Pre-Service Science Teachers’ Opinions About Being a Stem Teacher: A Pilot Study Based on the Perspective of Stem Teacher Identity - Eren, Emine (Research Trends In Educational Sciences, 2025)
With the integration of STEM, science education evolves into practices aiming at developing real-life problem solving, engineering, and design skills. This evolution reveals the importance of being a STEM teacher. Knowing how pre-service science teachers define being a STEM teacher and to what extent they identify themselves as a STEM teacher is very important for the future of science education. For this purpose, semi-structured interviews were conducted with 28 pre-service science teachers. The responses of the pre-service teachers were analyzed by content analysis. According to the findings, pre-service teachers think that teachers who effectively use technology and integrate it into their lessons, have sufficient content knowledge, and associate their knowledge with different disciplines are STEM teachers. Another important finding is pre-service teachers consider themselves STEM teachers in the future and have some motivations for this goal.